Wide Pulse Pressure Is Not Associated with Patent Ductus Arteriosus in the First Week of Life - Bin-Nun, Alona; Kasirer, Yair; Mimouni, Francis; Schorrs, Irina; Fink, Daniel; Hammerman, Cathy (American Journal of Perinatology, 2019)
Objectives Widened pulse pressure is generally associated with patent ductus arteriosus (PDA). Surprisingly, this is often not true for preterm infants during the first week of life when systolic and diastolic pressures are both reduced and pulse pressure may remain unchanged.Study Design This is a retrospective, observational review of individual blood pressure (BP) parameters preterm neonates <30 weeks' gestational age during the first week of life as correlated with ductal patency and severity.Results Sixteen preterm neonates had a closed ductus on initial echocardiogram during the first week of life; 30 had a PDA that was open but hemodynamically insignificant; and 16 were found to have a hemodynamically significant PDA. Pulse pressure showed no correlation (p = 0.266) with the degree of ductal patency, whereas diastolic BP was best correlated with ductal severity (p < 0.001).Conclusion We found that low diastolic pressures are better correlated with ductal patency and severity than is pulse pressure in preterm neonates during the first week of life.
Keywords: blood pressure; pulse pressure; patent ductus arteriosus; preterm neonate